The Effect of Educational Video-Based Multimedia toward Students’ English Vocabulary Mastery on 7th Grade Students at SMPN 52 North Bengkulu - Rahmatul Fadillah; Ferri Susanto; Dedi Efrizal (Jurnal Pendidikan dan Sastra Inggris, 2025)
This study aims to examine the effect of using educational video-based multimedia on the English vocabulary mastery of seventh-grade students at SMPN 52 North Bengkulu in the 2024/2025 academic year. This research uses a quantitative approach with a quasi-experimental design. The sample consisted of two classes: the experimental class received instruction using educational videos, while the control class was taught using traditional methods without multimedia support. Prior to the treatment, both groups were given a pre-test to measure their initial vocabulary ability. After the intervention, a post-test was conducted to assess the students’ vocabulary improvement. The data analysis revealed a significant increase in the post-test scores of the experimental group compared to the control group. This indicates that the use of video-based multimedia effectively enhances students’ vocabulary comprehension and retention. Additionally, video media improved students’ learning motivation and engagement during the instructional process. These findings recommend the integration of multimedia as an innovative strategy in English language teaching, particularly in vocabulary instruction, to create a more engaging, interactive, and contextual learning experience.